Parental Considerations in Choosing Early Childhood Education Institutions in RT/RW Neighborhoods in South Tangerang City - Mubarok, Indah Mustika Rahsya; Vijayanti, Ananda Muthia; Mundakir, Djizhilia Putri; Syafiqah, Nailah Jauzaa (Kiddie: Early Childhood Education and Care Journal, 2026)
The selection of Early Childhood Education (PAUD) institutions represents an important consideration for parents in supporting children’s optimal growth and development. This study aims to describe the factors considered by parents in selecting PAUD institutions within their local RT/RW community and to identify their expectations regarding the improvement of PAUD service quality. This study employed a descriptive qualitative approach. Data were collected through an open-ended questionnaire administered via Google Forms to five parents or guardians who served as research respondents. The data were analyzed using descriptive qualitative analysis by categorizing the responses into relevant thematic groups. The findings indicate that parents’ decisions in selecting PAUD institutions are primarily influenced by the quality of educational services in relation to children’s developmental needs, rather than solely by considerations of location and cost. The factors identified include teacher quality and competence, learning methods, educational facilities, school safety and comfort, location and accessibility, educational costs, as well as recommendations and experiences from family members and the surrounding community. Parents also identified several aspects requiring improvement, particularly the enhancement of learning methods, teacher competence, educational facilities, and the safety and cleanliness of the learning environment. Furthermore, parents expressed the need for more effective communication between PAUD institutions and parents.The findings highlight that service quality and parental trust constitute key considerations in the decision-making process for selecting a PAUD institution. This study contributes to providing an overview of the factors that should be considered by PAUD providers in developing services that are more responsive to children’s developmental needs and parents’ expectations.